Precision Machining Technology - Hoffman, Peter J. (Machinist); Hopewell, Eric S. (Boston : Cengage, 2020)
"Introduces students, both at the secondary and postsecondary levels, to the exciting world of precision machining technology as it is practiced in the 21st century"--Preface
Provides practical orientation that covers what students need to know about the field today. Develops modern interpersonal skills that are demanded by the job market. Covers current career information and trends. Includes modern shop practices. Contains specific instructions and examples, with images showing many step-by-step applications. Provides in-depth knowledge as a base for strong skills without being difficult to read or comprehend. Includes current computer numerical control (CNC) content with various programming examples
Section 1: Introduction to machining -- Section 2: Measurement, materials, and safety -- Section 3: Job planning, benchwork, and layout -- Section 4: Drill press -- Section 5: Turning -- Section 6: Milling -- Section 7: Grinding -- Section 8: Computer numerical control
Previous edition published 2015 as by Peter Hoffman, Eric Hopewell, Brian Janes
Includes index.
Keywords: Machine-tools -- Numerical control; Machining; Machine-tools